1113 Surgical Innovators or Spin Doctors: Reporting of Expectations for Robotic Gastrointestinal Surgery. (12th October 2021) - Dixon, L; Biggs, S; Turner, B; Embury-Young, Y; Wood, F; Leandro, L; Lok, P; Scroggie, D
Abstract: Introduction: The use of robotics in gastrointestinal surgery is an increasingly popular area of surgical innovation. Despite uncertainty regarding clinical benefits, gastrointestinal surgery centres continue to introduce robotic services. This may be motivated by perceived benefits, in lieu of substantial empirical benefits. We aimed to summarise the expected advantages and disadvantages of robotic techniques in gastrointestinal surgery, as reported by study authors. Method: A systematic review was undertaken by the trainee led RoboSurg Collaborative. Searches were conducted on of Embase, Medline, the Cochrane Library and Web of Science. Articles were double screened by abstract, then full text. All primary studies reporting outcomes following robotic cholecystectomy or oesophagectomy were included. Reports of expected benefits and disadvantages or robotic techniques were extracted verbatim, and summarised using descriptive statistics. Results: We included 192 studies. An expected benefit was reported in 161 (84%). Of those, 127 (79%) expected robotics to have an intra-operative advantage, such as reduced operative time, improved dexterity and improved visualisation. Post-operative benefits, such as reduced recovery time and shorter length of hospital stay, were expected in 72 (45%). Expected disadvantages were reported in 96 (50%) of the included studies. Of those, 74 (77%) expected robotics to have intra-operative disadvantages such as increased operative times and lack of tactile feedback. Increased cost was another commonly expected limitation. Conclusions: Study authors reported perceived benefits more frequently than disadvantages. Perceived benefits were more commonly advantageous to the surgeon rather than the patient. There were directly conflicting perceptions of how robotic techniques affect operative times.